Active pharmaceutical ingredients in dermatological medicines of Ukrainian pharmaceutical market - I. O. Vlasenko; L. L. Davtian (The State Expert Center of the Ministry of Health of Ukraine, 2019)
The problem of the diabetic foot is one of the most serious complications of diabetes mellitus. There is still an active search for medicines (drugs) that could be used in the complex treatment of trophic lesions in diabetic foot. The period before the development and launch of the drug into the pharmaceutical market need to make marketing research aimed at ensuring that the future drug is competitive. The purpose of the work was to analyze the market of dermatological drugs for the treatment of trophic ulcers in order to determine the marketing opportunities for domestic producers. The research objects were active pharmaceutical ingredients (APIs), which are part of the dermatological registered drugs in Ukraine. Materials for research were official sources of information about drugs registered in Ukraine. Marketing analytical methods were used. To determine the level of tension between manufacturers and the same product, the coefficient of tension. Number of D preparations registered in Ukraine ‒ 452 trade names (January 2018) was established. Medicines wich prodused by Ukraine are slightly higher (55.3%). In groups D01, D03, D06, D07 and D08 the highest number of APIs is determined, which is 25, 36, 33, 29 and 30, respectively. Part API is contained in the drug in combination with other API. In the D01 group, only a small amount of API ‒ 7 is present in combination with other substances, and in group D02 ‒ 6, certain APIs are part of the combined drug. In preparations of D03 4 API are in combination. In group D06, 12 APIs are contained in combination drugs. Most of the established API groups D07 (13) are found in the drug in combination. In the D08 group, part of the API (8) is part of a combined drug. There is a combination of APIs antiseptic or antimicrobial activity, anti-inflammatory effect, local anesthetic and wound healing effect. According to the results of the calculation of the tension indices between the manufacturers of analogues of drugs in group D, the highest competition (Kvi ≥ 0.800) was observed in the groups D01 and D03 (for 4 drugs with Kvi ≥ 0.800), D06 (3 drugs), D07 (8 drugs), D08 (7 drugs). An analysis of the competitiveness of analogue manufacturers has shown that Ukrainian manufacturers are not sufficiently competing in the production of modern analogues of dermatological drugs.